Value-distribution of twisted L-functions of normalized cusp forms - Kolupayeva, Alesia (Lietuvos matematikos rinkinys, 2010)
A limit theorem in the sense of weak convergence of probability measures on the complex plane for twisted with Dirichlet character L-functions of holomorphic normalized Hecke eigen cusp forms with an increasing modulus of the character is proved.